Hubungan Kepuasan Gaji dan Komitmen Organisasi terhadap Turnover Intention Karyawan RSIA MH di DKI Jakarta - Niluh Ayu Sri Saraswati; Imas Rosidawati; IGN Wiseto P. Agung (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
High employee turnover remains a critical issue in healthcare organizations, as it disrupts service continuity and increases operational costs. RSIA MH Jakarta experienced a turnover rate exceeding the acceptable threshold between 2021 and 2024, indicating potential problems related to compensation and employee attachment to the organization. This study aims to analyze the relationship between salary satisfaction and organizational commitment with employee turnover intention at RSIA MH Jakarta. A quantitative approach with a cross-sectional design was employed. Data were collected from 49 employees who met the inclusion criteria using structured questionnaires with a five-point Likert scale. Statistical analysis was conducted using correlation analysis and multiple linear regression with SPSS. The results indicate that salary satisfaction has a negative but statistically insignificant effect on turnover intention (β = -0.096, p = 0.592). In contrast, organizational commitment shows a significant negative effect on turnover intention (β = -0.796, p = 0.003). Simultaneously, salary satisfaction and organizational commitment significantly influence turnover intention (F = 8.804, p = 0.001), explaining 27.7% of the variance. These findings suggest that strengthening organizational commitment plays a more decisive role than salary satisfaction in reducing employee turnover intention in hospital settings.